THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE INFLUENCE OF PERCEIVED PRODUCT QUALITY AND BRAND IMAGE ON REPURCHASE DECISIONS AT ROMA TOP TEBING TINGGI - Sarwoto; Buaya, Nurhafizah; Hartanto, Bobby; Suci Etri Jayanti. S; Fitrianingsih (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The purpose of this research is to know the Influence of Perceived Quality Product And Brand Image On Repruchasing Decisions Through Customer Satisifications As Variabel Intervening At Roma Top Tebing Tinggi. This research was doing at Roma Top’s customer. The research was Descriptive and quantitative methods of data analysis. Sampling techniques used accidental sampling to decide 95 respondents. Data collection uses atechniques questionnaire. Data analysis methods using Structural Equation Model (SEM) based Partial Least Square (PLS 3.0). The result from Smart PLS 3.0 at this research : 1) Perceived Quality Product has a significant influence on Customer Satisfication. 2) Brand Image has a significant influence on Customer Satisfication. 3) Perceived Quality Product does not have significant influence on Repurchasing Decisions. 4) Brand Image has a significant influence on Repurchasing Decisions. 5) Customer Satisfications does not have a significant influence on Repurchasing Decisions. 6) Perceived Quality Product does not have a significant influence on Repurchasing Decisions through Customer Satisfication. 7) Brand Image does not have a significant influence on Repurchasing Decisions through Customer Satisfication